Diversity of the ribulose bisphosphate carboxylase/oxygenase form I gene (rbcL) in natural phytoplankton communities. - Pichard, S L (1997)
The phytoplankton of the world's oceans play an integral part in global carbon cycling and food webs by conversion of carbon dioxide into organic carbon. They accomplish this task through the action of the Calvin cycle enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). Here we have investigated the phylogenetic diversity in the form I rbcL locus in natural phytoplankton communities of the open ocean and representative clones of marine autotrophic picoplankton by mRNA or DNA amplification and sequencing of a 480 to 483 bp internal fragment of this gene. Five gene sequences were recovered from nucleic acids of natural phytoplankton communities of the Gulf of Mexico. The rbcL genes of two Prochlorococcus isolates and one Synechococcus strain (WH8007) were also sequenced. Sequences were aligned with the database of rbcL genes and subjected to both neighbor-joining and parsimony analyses. The five sequences from the natural phytoplankton community spanned nearly the entire diversity of characterized form I rbcL genes, with some sequences closely related to isolates such as Synechococcus and Prochlorococcus (forms IA and I) and prymnesiophyte algae (form ID), while other sequences were deeply rooted. Unexpectedly, the deep euphotic zone contained an organism that possesses a transcriptionally active rbcL gene closely related to that of a recently characterized manganese-oxidizing bacterium, suggesting that such chemoautotrophs may contribute to the diversity of carbon-fixing organisms in the marine euphotic zone.